Geology of the central part of the Amatrice Basin (Central Apennines, Italy). Issue 2 (3rd July 2019) - Vignaroli, G.; Mancini, M.; Bucci, F.; Cardinali, M.; Cavinato, G.P.; Moscatelli, M.; Putignano, M.L.; Sirianni, P.; Santangelo, M.; Ardizzone, F.; Cosentino, G.; Di Salvo, C.; et al.
ABSTRACT: A 1:5, 000 scale geological map and 31 geological cross-sections are presented for the surroundings of Amatrice village (central Apennines, Italy), epicentral area of the first damaging earthquake of the 2016–2017 seismic sequence. This detailed geological dataset focuses on: (i) the extent, the thickness, and the internal stratigraphic architecture of the Quaternary continental deposits; (ii) the bedding and the thickness of the Miocene substratum; and (iii) the spatial distribution of the main fault systems. The provided dataset would update the available regional geological maps in deciphering the syn-to-post-orogenic history of the Amatrice Basin. Eventually, the accuracy of the geological mapping would represent a basic tool for interpreting and integrating the multidisciplinary dataset deriving from post-seismic activities.